“Liberdade ainda que tardia”: Agnes Heller e a teoria das “necessidades radicais” frente à devassa da devassa brasileira - Veroneze, Renato Tadeu (2018)
The research aims to analyze "radical needs" in Agnes Heller's view as a contribution to understanding the cyclical and structural crises of capital, in the face of the wave of popular demonstrations and the political-economic crisis of the recent years that has affected Brazil, in particular. The choice of theme stemmed from the contradictions generated by these crises from the recognition of the values of freedom, democracy, equality, equity and social justice, in view of the principles established by its ethical-political-professional project of the Brazilian Social Service. In order to understand the limits and the personal, social and professional contradictions between the subjectivity and the objectivity of the individual and collective social subjects, as well as the social and professional limits and contradictions of the work of Agnes Heller, especially in her everyday life, lack and needs theories, and how to broaden the understanding of freedom and social and human emancipation that mark the emancipatory and revolutionary project of Social Service, having as motto a new sociability "beyond capital". The hypothesis raised here is that "radical needs" provoke the organization of civil society to overcome the status quo of social life tied to the destructive logic of capital, in order to understand the dynamics of social movements and popular manifestations, especially in Brazil, as a mobilization of resistance against the Brazilian political-economic crisis and the macrocorruption scheme that has been established in the country's political and economic system. Through a theoretical-conceptual analysis, based on the Marxian legacy and the Marxist tradition, we start from the thesis that it will only be possible to demolish the existing barriers between working time and non-working time, through the organization of civil society revolutionary subject. Only in this way will revolutionary social changes be realized for the anti-capitalist and anti-imperialist struggles. It is in this direction that Agnes Heller points to a new collective revolutionary subject. The "radical needs" are all those that are born in capitalist society as a consequence of the development of civil society, and that can not be satisfied within the limits of the same, which implies in factors that can lead to the overcoming of capitalism, the wage relationship, the concentration of private property, the class struggle and the loss of the bourgeois state. Only on these bases, of a totally new sociability, we do believe that social individuals can fully develop themselves ("wholly and entirely"), in which work, sociability, consciousness, freedom, ethics, art, philosophy, truly free time and idleness are in conformity with the most authentic aspirations raised within the everyday life and in the valuation of the feeling of community as an ontological-social value. We start from these assumptions because, with the precarization and flexibilization of labor relations, outsourcing, globalization, robotics, new technologies, the increase of the service sector, among other vectors, have caused significant changes in the social body of the working class and in their leadership. Thus, in Agnes Heller's view, it is only with the organization of civil society that it will be possible to destroy the overwhelming and destructive wave of capitalism